Antibiotic Sensitivity of Staphylococcus aureus and Staphylococcus epidermidis Isolated from Acne Patients - Khan, Ashfia Fatima; Hana, Humayera Kabir; Sheak, Jakaria; Begum, Kohinur (Bangladesh Pharmaceutical Journal, 2015)
In this study, twenty five samples were collected from acne, ranging from 20 to 25 years old patients. The specimens were cultured on trypticase soy agar (TSA) plate. 25 suspected single colonies were isolated using mannitol salt agar. Isolates were identified by short biochemical tests such as catalase, coagulase, oxidase and Gram staining test. Five Staphylococcus aureus and eleven Staphylococcus epidermidis strains were identified. Antibiotic sensitivity of all strains was tested according to the Kirby-Bauer method using commercially available gentamicin, erythromycin, azithromycin, oxacillin, clindamycin and rifampicin discs. 100% of the isolates were sensitive to gentamicin and rifampicin. On the other hand, 93.75% isolates were sensitive to oxacillin, erythromycin and azithromycin and 81.25% isolates were sensitive to clindamicin. Minimum inhibitory concentration (MIC) of rifampicin and gentamicin was determined by test tube serial dilution method and it was found to be 4 ?g/ml for both. Our results showed that both rifampicin and gentamicin are effective antibacterial agents for acne. Bangladesh Pharmaceutical Journal 18(2): 121-125, 2015